SOFTWARE ENGINEERING FOR ZAKAT MANAGEMENT PLATFORMS: A STUDY ON TRANSPARENCY, SECURITY, AND USER TRUST - Zuraida Zuraida; Rina Farah; Hilda Dwi Yunita (Journal of Moeslim Research Technik, 2025)
The management of zakat is crucial in Islamic finance, and digital platforms have increasingly been adopted to enhance transparency, security, and trust among users. This study examines the software engineering aspects of zakat management platforms, focusing on these critical dimensions. The research aims to identify key software design considerations that can improve transparency, ensure data security, and foster user trust within digital zakat platforms. A mixed-method approach is used, involving both qualitative interviews with zakat management professionals and quantitative analysis of platform users' perceptions. The findings suggest that clear communication regarding financial transactions, robust data protection measures, and user-friendly interfaces are essential for building trust. Furthermore, implementing blockchain technology was found to significantly enhance transparency and security. The study concludes that for zakat platforms to be successful, they must not only comply with Shariah principles but also integrate advanced technology solutions that align with user expectations for security and transparency. This research provides a comprehensive framework for the development of zakat management platforms that can be adopted by stakeholders in the Islamic finance sector.